Biosynthesis of cannabinoids by heterologous expression in microorganisms downstream development and in silico sensitivity analysis of metabolic pathways - Favero, Gabriel Rodrigues, 1993- (2022)
Orientador: Prof. Dr. Gilberto Vinícius de Melo Pereira